Translating policy guidelines: a multiple case study of disease prevention in Sweden - Mattias Elg; Elin Wihlborg; Malin Wiger (BMC Health Services Research)
Abstract Background There is a growing need for new knowledge about healthcare policy implementation that is relevant to both researchers and practitioners. Many policy initiatives fail due to insufficient coordination between different system levels and conflicting agendas among various actors. This paper aims to propose and illustrate an analytical framework using a multilevel-multilogic framework. This framework helps reveal the combined challenges encountered when implementing policies within public healthcare systems. Methods A multiple case study was conducted, focusing on the implementation of disease prevention guidelines in four Swedish healthcare regions. These regions were purposefully selected to represent diverse contexts and conditions that could influence policy translation. A total of 28 respondents across the four regions were interviewed, representing different system levels and institutional logics. The qualitative analysis identified connections between actors, settings, and policies, and explored how policy translation varied—from strong to weak, or even interrupted—as it moved from policy development to clinical practice. Results We developed a theoretical and empirical understanding of policy translation processes, tracking how evidence-based national guidelines for disease prevention methods (DPMs) moved through regional administrative systems into clinical practice. The analysis focused on four main themes: the gradual translation and reinterpretation of policy objectives, the impact of shifting policy priorities, the facilitating role of technology in translation processes, and the ways policy became embedded into everyday clinical routines. Conclusions Policy guidelines are implemented through a stepwise translation process, first being adopted and adapted within healthcare administrative systems via political and administrative activities, and then integrated into clinical practice. Within the multilevel-multilogic framework, each system level or logic has the potential to adapt, alter, delay, or even block the intended policy. Actions taken early in the translation process significantly affect the outcomes of subsequent stages.